Penyelesaian Sengketa Tanah Warisan Melalui Mediasi Terhadap Kedudukan Anak Angkat Dalam Sistem Pewarisan di Bali (Studi Kasus Desa Adat Dalung) - Rai Dharma Utama; I Nyoman Putu Budiartha; Diah Gayatri Sudibya (Fakultas Hukum Universitas Warmadewa, 2025)
Inheritance land dispute is a problem that occurs due to the dissatisfaction of the heirs regarding the distribution of the inheritance inherited by the testator. This study is interesting to the following questions: 1) How to resolve inheritance disputes over the position of adopted children in the inheritance system in Bali? and 2) What are the causes of inheritance disputes in the inheritance system in Bali?. The purpose of the study is to understand the factors that cause the occurrence of Inherited Land Disputes, to find out the efforts to resolve Inherited Land Disputes Against the Position of Adopted Children ON the Inheritance System in Bali. This study uses an empirical legal research method by conducting direct research to Dalung Village, conducting interviews with informants at the location. The results of the study show that the factors that cause inheritance disputes in the inheritance system in Bali are that there are various parties who are dissatisfied with the distribution of inheritance, Dispute resolution efforts that can be carried out are through mediation, carried out by both parties to the dispute accompanied by kelian as a mediator